Records of Psocidae: Psocinae (Insecta: Psocoptera) from Sumatra, Indonesia - Kentjonowati, Endang Sri; New, T. R. (Zootaxa, 2010)
Twelve species of Psocidae: Psocinae are recorded from Sumatra. Two, Psocidus strictus Thornton and Atrichadenotecnum umbratum (New & Thornton), are the first records from Indonesia, whilst all others were known previously from eastern Indonesia. Distributions and affinities are discussed.